PENGARUH MODEL CORE TERHADAP HASIL BELAJAR SISWA PADA MATERI HIDROLISIS GARAM KELAS XI SMA - Septi Dwi Listiani; Hairida Hairida; Rahmat Rasmawan (Universitas Tanjungpura, 2020)
Abstract The aim of this research is to determine the influence of the CORE model on student learning outcomes on the Salt Hydrolysis material at SMAN 2 Mempawah. The form of research is used a quasi experimental design with a nonequivalent control group design. The sample was XI MIPA 1 as an experimental class totaling 27 students and XI MIPA 2 as a cotrol class totaling 24 students, with a population totaling 51 students. Data collection techniques that are data measurement techniques, direct communication, observation with data collection tools in the form of learning outcomes tests, interview guidelines and observation sheets. The indicator in this research are to determine the equation of the reaction of salt hydrolysis, determine the acidic nature of a salt solution, and calculate the pH of the salt solution based on discourse. Based on the analysis using the Mann Whitney U test (? = 5%) that is 0.000 ? 0.05 shows that there are differences in learning outcomes between students who are taught using the CORE model and students who are taught using conventional methods. The value of the effect size obtained was 1.31 and gave an effect of 40.49% to the increase in student learning outcomes. Keywords: CORE, learning outcomes, salt hydrolysis